Socioeconomic aspects of the production chain of species Cardisoma guanhumi in the Northeast coast of Brazil - Cavalcanti, Brunna de Andrade Lima Pontes; Silva, Daywison Borges da; Silva, Leandro Muniz Barbosa da; Rodrigues, Gilberto Gonçalves (Journal of Environmental Analysis and Progress, 2019)
Mangroves are considered an important coastal ecosystem for feeding, protecting and breeding many species. Crustaceans constitute one of the most important groups of mangrove fauna, among the species traded in Brazil, Cardisoma guanhumi (Guaiamum) stands out. In recent years, there has been a decline in the populations of C. guanhumi in Brazil and the species has come to be considered as critically endangered, remaining in this category until today. The species plays an important role in the local ecosystem and social dynamics, the risk of extinction may lead to several negative social and environmental impacts. Aiming at this problem, the research aimed to characterize the socioeconomic representation of this activity. The methodological procedures focused on bibliographical, documentary and cartographic review. For the identification of the flows linked to the production chains, the participant observation technique was used, accompanying the scavengers in their work environments, the transport and commercialization transporters to the final destination. The results point to the identification of two flows (internal and external) that help to understand how the productive chain has been structured. The new modes of production have interfered in the social aspects of the productive chain of the species, being able to accentuate the situation of social vulnerability in which are inserted the social actors that depend on their harvesting. Therefore, it is necessary to create policies and instruments of governance for these territories that aim at planning, planning and environmental management for the regulation of the use of the species considering the aspects of local social dynamics.